2017
DOI: 10.1155/2017/8765972
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Singlet Oxygen to Insulin Resistance

Abstract: Insulin resistance contributes to the development of diabetes and cardiovascular dysfunctions. Recent studies showed that elevated singlet oxygen-mediated lipid peroxidation precedes and predicts diet-induced insulin resistance (IR), and neutrophils were suggested to be responsible for such singlet oxygen production. This review highlights literature suggesting that insulin-responsive cells such as endothelial cells, hepatocytes, adipocytes, and myocytes also produce singlet oxygen, which contributes to insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 124 publications
0
37
0
3
Order By: Relevance
“…IR is a major contributory mechanism for diabetes . During the postprandial state, insulin secretion from pancreatic β‐cells controls systemic plasma glucose homeostasis by promoting anabolic processes in liver cells . Previous reports have shown that phosphorylation of IRS1 at Ser 307, which antagonizes Akt‐ser 473 phosphorylation, leads to IR and increased plasma glucose .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IR is a major contributory mechanism for diabetes . During the postprandial state, insulin secretion from pancreatic β‐cells controls systemic plasma glucose homeostasis by promoting anabolic processes in liver cells . Previous reports have shown that phosphorylation of IRS1 at Ser 307, which antagonizes Akt‐ser 473 phosphorylation, leads to IR and increased plasma glucose .…”
Section: Discussionmentioning
confidence: 99%
“…17 During the postprandial state, insulin secretion from pancreatic β-cells controls systemic plasma glucose homeostasis by promoting anabolic processes in liver cells. 17,18 Previous reports have shown that phosphorylation of IRS1 at Ser 307, which antagonizes Akt-ser 473 phosphorylation, leads to IR and increased plasma glucose. 19,20 In our experiments, Res relieved ER stress and ROS generation and CYP enzymes expressed throughout the human body play a crucial role in human physiology and are involved in drug and xenobiotic metabolism as well as biosynthesis of endogenous molecules.…”
Section: Tio 2 Nps Induce Insulin Resistance and Elevation Of Plasmmentioning
confidence: 99%
“…Chrysin ( (Onyango, 2017;Sarangi et al, 2012). The inactivation of RAGE ameliorates the myocardial ischemic and progression of atherosclerosis in the diabetic patients (Suchal et al, 2017;Yamagishi & Matsui, 2018).…”
Section: Cardiovascular Complications Of Diabetesmentioning
confidence: 99%
“…insulin resistance -IR) -oznacza zmniejszoną wrażliwość tkanek na działanie insuliny, często powodującą pojawienie się innych zaburzeń w gospodarce węglowodanowej. 17…”
Section: Rodzaje Zaburzeń Metabolizmu Węglowodanówunclassified